Interprofessional education and practice guide No. 5: Interprofessional teaching for prequalification students in clinical settings. Issue 3 (3rd May 2016) - Lie, Désirée A.; Forest, Christopher P.; Kysh, Lynn; Sinclair, Lynne
ABSTRACT: The importance of interprofessional education in health professions training is increasingly recognised through new accreditation guidelines. Clinician teachers from different professions may find themselves being asked to teach or supervise learners from multiple health professions, focusing on interprofessional dynamics, interprofessional communication, role understanding, and the values and ethics of collaboration. Clinician teachers often feel prepared to teach learners from their own profession but may feel ill prepared to teach learners from other professions. In this guide, we draw upon the collective experience from two countries: an institution from the United States with experience in guiding faculty to teach in a student-run interprofessional clinic and an institution from Canada that offers interprofessional experiences to students in community and hospital settings. This guide offers teaching advice to clinician educators in all health professions who plan to or already teach in an interprofessional clinical setting. We anticipate that clinician teachers can learn to fully engage learners from different professions, precept effectively, recognise common pitfalls, increase their confidence, reflect, and become role models to deliver effective teaching in interprofessional settings.